Chronic pelvic pain as a female problem - I V Kuznetsova (Гинекология, 2017)
Chronic pelvic pain occurs mainly in women, and is therefore often regarded as a symptom of a gynecological disease. Meanwhile, the causes of chronic pelvic pain are usually multiple, and its formation is associated primarily with the persistence of estrogen-dependent inflammation and the development of peripheral and central sensitization of the nervous system. The presence of estrogen-dependent inflammation explains, on the one hand, the female privilege of pain, and, on the other hand, the frequent detection of endometriosis in patients with chronic pelvic pain. At the same time, the actualization of the problem of chronic pelvic pain as the main goal of treatment allows us to make a reasonable choice of means to improve the quality of life of patients.